Comparative study of Taqman-based qPCR assay for the detection of Anisakis simplex and Pseudoterranova decipiens - Mi-Gyeong Kim; Min Ji Hong; Doo Won Seo; Hyun Mi Jung; Hyun-Ja Han; Seung Hwan Kim; Insun Joo (PLoS ONE, 2025)
Anisakidosis is a foodborne parasitic infection caused by the consumption of raw or uncooked seafood that contains third stage larvae from the Anisakidae family. This infection has been observed across the globe, with a particularly high prevalence in South Korea and Japan. Consequently, there is a necessity to compare and analyze the optimal detection methods with a view to preventing Anisakis outbreaks. In this study, a species-specific Taqman-based qPCR method was developed for the detection of the internal transcribed spacer region and mtDNA genes of Anisakis simplex and Pseudoterranova decipiens. Parasite-specific primer/probe sets were selected based on the data from domestic and foreign detection methods. In addition, we have designed our own primer/probe sets based on the target region of each parasite. A comprehensive literature review and a self-creation process were undertaken to select thirteen detection method sets for A. simplex and P. decipiens. The sensitivity of these sets was then evaluated by comparing the Cq values from extracted DNA. The concentrations of six primer/probe sets detected through the screening process were then compared to optimize the test method. The resultant optimized method demonstrated a limit of detection of 0.0019 ng/µL for A. simplex and 0.0001 ng/µL for P. decipiens. The specificity test also confirmed that there was no cross-activity with the five parasite samples and the three types of anisakids plasmid DNA. This study would contribute development of a rapid detection method for anisakidosis, providing a foundation for proactive responses to food poisoning outbreaks.